Antibacterial, Kinetics and Bacteriolytic Properties of Silver(I) Pyridinedicarboxylate Compounds - Paez-Collio, M; Paez-Collio, M; Azocar-Guzman, M; Azocar-Guzman, M (2014)
Antibacterial properties of silver(I)-pyridinedicarboxylate compounds (with Pyridine-2,3-dicarboxylic(Lutidinic acid), pyridine-2,4-dicarboxylic (Quinolinic acid) and pyridine-2,5-dicarboxylic (Isocinchomeronic acid)) were studied against Escherichia coli, Listeria monocytogenes (ISP-65-08), Salmonella typhi and Staphylococcus aureus (ATCC 25923) using kinetics of grown inhibition, viability assays, minimum inhibitory concentration and optical microscopy. The 3 silver compounds were tested toward UV-radiation in order to characterize their light insensitivity for potential medical devices: UV-radiation curable polymers. Photophysical measurements show remarkable differences toward UV-radiation, which were explained based on their polymeric structures with multiple nature bonds between pyridinedicarboxylic ligands and Ag(I) centers. We found a bacteriolytic effect and differences in the antibacterial efficiency depending on the structure of the complexes and the nature of AgX (X = oxygen and nitrogen) bonds: AgQuinol > AgLutidin > AgIsocinchom. © 2014 Elsevier B.V.